1992
DOI: 10.1136/adc.67.4_spec_no.443
|View full text |Cite
|
Sign up to set email alerts
|

Intracardiac thrombus formation with rapidly progressive heart failure in the neonate: treatment with tissue type plasminogen activator.

Abstract: A newborn is described in whom the use of a central venous line was complicated by septicaemia and by intracardiac thrombus formation with tricuspid valve insufficiency and heart failure. Besides antibiotics, treatment consisted of tissue type plasminogen activator (tPA) for three days. This treatment resulted in the disappearance of the thrombus and the tricuspid insufficiency. No adverse effects were noted. Treatment with tPA should be considered in intracardiac thrombus formation with rapidly progressive h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 12 publications
0
29
0
Order By: Relevance
“…1 If the catheters are positioned within the heart, damage to the endocardium can induce the development of intracardial thrombi despite a normal heart structure. 3 In the presence of IE, it is frequently impossible to eliminate the infection with removal of the infected line and antibiotic treatment alone, and persisting sepsis, despite adequate treatment with appropriate antiinfective agents, is an indication for surgical intervention. The development of infected intracardiac vegetations (infective endocarditis [IE]) secondary to line infection exposes the infant to prolonged infection and the dissemination of septic emboli to distant organs.…”
mentioning
confidence: 99%
“…1 If the catheters are positioned within the heart, damage to the endocardium can induce the development of intracardial thrombi despite a normal heart structure. 3 In the presence of IE, it is frequently impossible to eliminate the infection with removal of the infected line and antibiotic treatment alone, and persisting sepsis, despite adequate treatment with appropriate antiinfective agents, is an indication for surgical intervention. The development of infected intracardiac vegetations (infective endocarditis [IE]) secondary to line infection exposes the infant to prolonged infection and the dissemination of septic emboli to distant organs.…”
mentioning
confidence: 99%
“…This might have some importance in the premature infant with physiologically low plasminogen and fibrinogen concentrations. [44] Amazingly, despite these advantages, tPA has only rarely been used in preterm infants with vena cava or intracardiac thrombosis (table I) [27,39,60] and it is only recently that two different groups reported the successful use of rt-PA in small series of neonates or preterm infants, respectively, with catheter-related thrombosis. [41,64] Bleeding complications were reported only by one group in a small number of patients.…”
Section: The Choice Of Thrombolytic Agentmentioning
confidence: 98%
“…Although no clinical trials of thrombolytic treatment in neonates have been reported, there are many case reports suggesting that thrombolytic treatment may be efficient in treating intracardiac thrombosis in neonates born at term and in preterm infants [20,[22][23][24][25]27,28,33,[37][38][39]41] (table I).…”
Section: Medical Treatmentmentioning
confidence: 99%
“…Large intraatrial thrombi, whether located on the endocardium or at the catheter tip, may result in major complications, such as acute superior vena cava obstruction, pulmonary embolization, endothelial injury, infective endocarditis, tricuspid valve insufficiency, or cardiopulmonary arrest (3)(4)(5). In cases in which the thrombus is large or complications occur, surgical removal of the catheter by atriotomy under cardiopulmonary bypass may become necessary (1,4).…”
mentioning
confidence: 99%